2010
DOI: 10.1111/j.1467-9507.2009.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Knowledge, Social Competence, and Behavior Problems in Childhood and Adolescence: A Meta-analytic Review

Abstract: The present meta-analytic review examined the magnitude of the relation between discrete emotion knowledge and three of its most commonly studied correlates in childhood and adolescence: social competence, internalizing problems, and externalizing problems. Emotion knowledge demonstrated small to medium-sized relations with each correlate. Moderators of effect size were also examined and included multiple sample and methodological characteristics. Using random effects models, significant moderators of effect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
284
2
27

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(333 citation statements)
references
References 100 publications
20
284
2
27
Order By: Relevance
“…Inaccuracies in understanding one's own and other's emotions and a propensity to see other's as angry and hostile have been found in children with behavior difficulties (Eisenberg et al 2001;Trentacosta and Fine 2010). These children have also been found to have poor emotion regulation, social skills difficulties (Morris et al 2010;Olson et al 2011;Trentacosta and Shaw 2009) and greater negative emotionality (Eisenberg et al 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Inaccuracies in understanding one's own and other's emotions and a propensity to see other's as angry and hostile have been found in children with behavior difficulties (Eisenberg et al 2001;Trentacosta and Fine 2010). These children have also been found to have poor emotion regulation, social skills difficulties (Morris et al 2010;Olson et al 2011;Trentacosta and Shaw 2009) and greater negative emotionality (Eisenberg et al 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Measures of social competence include observed or reported levels of social skills, social preference, peer status, pro-social behaviour, or developmentally appropriate social play behaviour (e.g., social pretend or co-operative play for preschoolers) (Trentacosta and Fine, 2010). Guttman (1984) found that boys who owned a companion animal performed better on measures of their capacity for decoding non-verbal information, potentially making them better at communication, than boys who did not.…”
Section: Social Developmentmentioning
confidence: 99%
“…The ability to understand emotion is also seen as a mediator between emotional perception abilities and emotion regulation mechanisms (Joseph & Newman, 2010;Salovey, Bedell, Detweiler & Mayer, 1999). In their influential meta-analysis, Trentacosta & Fine (2010) showed weak to moderate positive correlations of emotion understanding and general social competence, and similar in magnitude -although negative -relations with internalized and externalized problems in children and youth. Considering emotion understanding as a part of emotional intelligence, other important correlates of higher levels of emotion understanding are greater social competence, better life quality, social sensitivity, better perceived social support from parents and friends, and lower tendency towards antagonistic and aggressive relations with friends and people in general (Brackett, Warner & Bosco, 2005;Brackett et al, 2006;Lopes, Salovey, Cote & Bears, 2005;Lopes et al, 2003Lopes et al, , 2004Rubin, 1999).…”
Section: Emotion Understandingmentioning
confidence: 99%